Intellectual capital, knowledge management and competitive advantage: a resource orchestration perspective - Rehman, Shafique Ur; Bresciani, Stefano; Ashfaq, Khurram; Alam, Gazi Mahabubul (Emerald Insight, 2022)
Purpose: This study aims to examine the influence of intellectual capital and knowledge management on competitive advantage with the mediation role of innovativeness in the Pakistan manufacturing industry. Moreover, differentiation strategy is used as a moderator between innovativeness and competitive advantage. Design/methodology/approach: The data was collected from 387 manufacturing firms in Pakistan through questionnaires. Purposive random sampling was used to collect data. The partial least square structural equation modeling (PLS-SEM) method is used to test the proposed hypotheses. This study followed multiple regression analyses to see the influence of intellectual capital, knowledge management, innovativeness and differentiation strategy on competitive advantage. Findings: The results elucidate that intellectual capital and knowledge management significantly determines innovativeness and competitive advantage. Moreover, innovativeness significantly mediates between intellectual capital, knowledge management and competitive advantage. Besides, innovativeness significantly determines competitive advantage. Business strategies significantly lead to competitive advantage. Finally, business strategies significantly moderate between innovativeness and competitive advantage. Practical implications: The research highlight an important issue that how manufacturing sector management uses intellectual capital, knowledge management, innovativeness and business strategies in determining competitive advantage. Besides, it covers the gap and assists the management of the manufacturing sector to focus on exogenous constructs to examine competitive advantage. Originality/value: This study adds value to the body of knowledge by focusing on predictors that impact competitive advantage. This initial study determines intellectual capital and knowledge management influence on competitive advantage and innovativeness as a mediator by using resource orchestration theory. Moreover, differentiation strategy is used as moderating variable between innovativeness and competitive advantage. The managers, students and researchers can obtain benefits from this study.